Assessment of Adult Women With Ovarian Masses and Treatment of Epithelial Ovarian Cancer: ASCO Resource-Stratified Guideline. Issue 2 (February 2022) - Vanderpuye, Verna D.; Clemenceau, Jean Rene V.; Temin, Sarah; Aziz, Zeba; Burke, William M.; Cevallos, Nixon Leonardo; Chuang, Linus T.; Colgan, Terence J.; del Carmen, Marcela G.; Fujiwara, Keiichi; Kohn, Elise C.; Nogales, Jose Enrique Gonzáles; et al.
Abstract : (Abstracted from JCO Glob Oncol 2021;7:1032–1066) The lack of reliable screening modalities for ovarian cancer results in most women being diagnosed on the basis of symptomatic presentation with the majority at advanced stages. Nonspecific symptoms may be overlooked or misdiagnosed regardless of how resource-rich the health care system.